THE FRAMEWORK FOR EFFECTIVE SAFETY CONTROL AND IMPLEMENTATION AT CONSTRUCTION PROJECT - Othman, Idris; Mohamad, Hisham; Napiah, Madzlan; Hashim, Zain; Cai, Zuansi (International Journal of Engineering Technologies and Management Research, 2018)
The Construction industry enhanced the growth of socio-economic of country as well as providing the necessary infrastructure and enhanced facilities for social comfort. However, it is stigmatized as the most hazardous industries due to high occupational risks and unsatisfactory state of occupational safety. Therefore, this study evaluates the factors affecting the successful implementation of safety control practices in construction project through structured questionnaire and case study of high rise construction project. The statistical techniques including Relative Importance Index (RII) and Average Index (AVI) are used to analyse the data gathered, while the statistical package for the social sciences (SPSS) is used to measure the Spearman’s rank correlation between four different groups of respondents, the Cronbach’s alpha (reliability test) and validity of the study. The high impact factors identified are then validated with the case study on contractors’ practitioners’ practices. Based on the highest impact factors identified, a framework of safety control management was proposed to improve the safety performance at construction project. The study concludes with the conclusion on the data obtained and recommendation for the improvement, thus more valid and reliable results can be obtained for the implementation of safety control practices in construction project.